“Compromisso da Irmandade do Senhor Bom Jesus do Cuiabá : edição e estudo filológico” - Lima, Marisa Soares de (2013)
This paper aims to present a philological study of nineteenth-century codex-1821- called "Commitment of the Brotherhood of the Good Lord Jesus of Cuiabá," consists of 42 papers, some front and verse, in good condition cover conservation, protected Institute for Historical Geography of Mato Grosso - IHGMT. This document is a kind of charter of this organization of a religious character, with the training content rules that guide as well as signatures from members and leaders. In this regard were held copy editions and semi diplomatic presented in translated, including analysis also paleographic, codicological and social-historical marking the time when the document was produced. The interest for this work came with it because there are chances of recovery of cultural heritage written and thus contribute to the preservation of the same, return the text to its genuineness, seeking the closest possible to the true will of the author and contribution to studies linguistic and historical heritage of Brazilian Portuguese. Worth noting that also for historical, linguistic and cultural. so it must be adopted as a theoretical and methodological principles of Philology, according to the approach taken by Acioli (2003), Cambraia (2005 ), Spina (1994), among others.